2004
DOI: 10.1007/1-4020-2591-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Mapping of Winter Hardiness Metabolites in Autotetraploid Alfalfa (M. sativa)

Abstract: In winter hardy alfalfa cultivars, cold acclimation occurs prior to the onset of freezing temperatures and normally is accompanied with a series of metabolic and morphological adjustments. We are studying the accumulation pattern of metabolites throughout the autumn previous to free zing and relating them to winter survival in an Fl segregating population between the cross of M. sativa subsp. sativa and subsp. falcata. Morphological components and soluble carbohydrates, protein, amino-N groups, and free fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Genetic linkage maps have been constructed in both diploid ( M. truncatula ) and tetraploid alfalfa ( M. sativa ) using various marker platforms including restriction fragment length polymorphism (RFLP), simple sequence repeat (SSR), random amplified polymorphic DNA (RAPD), and amplified fragment length polymorphism (AFLP) markers. QTLs associated with biomass (Robins et al, 2007b ), morphological traits (Robins et al, 2007a ), winter hardiness, persistence (Brouwer et al, 2000 ; Alarcón-Zúñiga et al, 2004 ), self-fertility (Robins and Brummer, 2010 ), Stagonospora root and crown rot resistance (Musial et al, 2007 ), anthracnose resistance (Mackie et al, 2007 ) and aluminum tolerance (Khu et al, 2010 ) have been identified in alfalfa. QTLs associated with salt tolerance have been identified in the model legume, M. truncatula and mapped to all chromosomes except chromosomes 5 and 6 (Arraouadi et al, 2011 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic linkage maps have been constructed in both diploid ( M. truncatula ) and tetraploid alfalfa ( M. sativa ) using various marker platforms including restriction fragment length polymorphism (RFLP), simple sequence repeat (SSR), random amplified polymorphic DNA (RAPD), and amplified fragment length polymorphism (AFLP) markers. QTLs associated with biomass (Robins et al, 2007b ), morphological traits (Robins et al, 2007a ), winter hardiness, persistence (Brouwer et al, 2000 ; Alarcón-Zúñiga et al, 2004 ), self-fertility (Robins and Brummer, 2010 ), Stagonospora root and crown rot resistance (Musial et al, 2007 ), anthracnose resistance (Mackie et al, 2007 ) and aluminum tolerance (Khu et al, 2010 ) have been identified in alfalfa. QTLs associated with salt tolerance have been identified in the model legume, M. truncatula and mapped to all chromosomes except chromosomes 5 and 6 (Arraouadi et al, 2011 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an allele al from a cold related gene MSAIC B showed correlation with autumn plant regrowth height in the cultivar WISFAL-6 [90]. Recent progress in next generation sequencing enabled the understanding of the genetic basis of complex traits like dormancy.…”
Section: Genetic Control Of Dormancymentioning
confidence: 99%
“…Selection based on molecular markers offers one means of decreasing the cycle time, and we are attempting to identify loci associated with these traits using standard genetic mapping and QTL detection procedures (Robins et al, 2003). In addition to mapping these ultimate phenotypes, we are dissecting both traits by concurrently mapping morphological and physiological components, such as sugar, starch, and protein content in roots during autumn (Alarcón‐Zúñiga et al, 2004). Our hope is that these component traits, which may have a simpler genetic basis, will allow us to manipulate the overall complex trait in a targeted, modular manner.…”
Section: Acknowledgmentsmentioning
confidence: 99%